2016
DOI: 10.1038/ejhg.2016.91
|View full text |Cite
|
Sign up to set email alerts
|

Rare novel variants in the ZIC3 gene cause X-linked heterotaxy

Abstract: Variants in the ZIC3 gene are rare, but have demonstrated their profound clinical significance in X-linked heterotaxy, affecting in particular male patients with abnormal arrangement of thoracic and visceral organs. Several reports have shown relevance of ZIC3 gene variants in both familial and sporadic cases and with a predominance of mutations detected in zinc-finger domains. No studies so far have assessed the functional consequences of ZIC3 variants in an in vivo model organism. A study population of 348 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…A study in ZIC3 mutants overexpressing either wild-type ZIC3 mRNA or mutant ZIC3 mRNA showed that overexpression of wild-type ZIC3 mRNA resulted in cardiac laterality defects, posterior truncation or embryo lethality. However, the examined mutants (p.Val288Serfs*50, p.His281Argfs*62, p.Asn371His) exhibited less extensive phenotypes, indicating a partial loss of function 31 . To confirm the role of Zic3 in establishing LR asymmetry, we used an antisense MO to knockdown the expression of zebrafish zic3 .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…A study in ZIC3 mutants overexpressing either wild-type ZIC3 mRNA or mutant ZIC3 mRNA showed that overexpression of wild-type ZIC3 mRNA resulted in cardiac laterality defects, posterior truncation or embryo lethality. However, the examined mutants (p.Val288Serfs*50, p.His281Argfs*62, p.Asn371His) exhibited less extensive phenotypes, indicating a partial loss of function 31 . To confirm the role of Zic3 in establishing LR asymmetry, we used an antisense MO to knockdown the expression of zebrafish zic3 .…”
Section: Discussionmentioning
confidence: 92%
“…The mutant ZIC3 construct was generated from the wild-type ZIC3 plasmid via site-directed mutagenesis and contained a C-terminal Myc-tag. The wild-type and mutant ZIC3 constructs were subsequently co-transfected into the NIH/3T3, H9C2, and 293T cell lines with an SV40 promoter-driven firefly luciferase reporter 22 , 31 . Our results showed that the ZIC3 mutation in the C2H2 domain significantly decreases reporter gene transactivation compared with the wild-type controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All types of inheritance including Xlinked, autosomal dominant, and autosomal recessive have been described with multiple implicated genes including LEFTYA, CRYPTIC, and ACVR2B (Belmont et al 2004). Pathogenic variants in ZIC3, a zinc-finger transcription factor involved in heart looping, are thought to contribute to ∼5% of HTX cases in males (Cowan et al 2014;Paulussen et al 2016).…”
Section: Heterotaxy and Ciliopathiesmentioning
confidence: 99%